2022
DOI: 10.1038/s41598-022-20963-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ivabradine on cognitive functions of rats with scopolamine-induced dementia

Abstract: Alzheimer’s disease is among the challenging diseases to social and healthcare systems because no treatment has been achieved yet. Although the ambiguous pathological mechanism underlying this disorder, ion channel dysfunction is one of the recently accepted possible mechanism. Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels play important roles in cellular excitability and synaptic transmission. Ivabradine (Iva), an HCN blocker, is acting on HCN channels, and is clinically used for angina a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…The present results are similar to those of Assi et al, who demonstrated that SCO reduced memory function (33). Administration of SCO enhanced Aβ plaques in the rat hippocampus (25).…”
Section: Discussionsupporting
confidence: 93%
“…The present results are similar to those of Assi et al, who demonstrated that SCO reduced memory function (33). Administration of SCO enhanced Aβ plaques in the rat hippocampus (25).…”
Section: Discussionsupporting
confidence: 93%
“…Scopolamine, dissolved in physiological saline, was intraperitoneally injected (I.P.) at a dose of 4 mg/kg, once a day for 28 days (Assi et al 2022 ). Rats received the heavy metals mixture (HMM) through their drinking water throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…SCO dissolved in saline was injected I. P. at a dose of 4 mg/ kg once a day for 28 consecutive days. The rats also received an HMM through their drinking water during the experiment, with As at 3.80 parts per million (ppm), Cd at 0.98 ppm, and Pb at 2.22 ppm [30,53]. Water consumption was measured throughout the study period.…”
Section: Experimental and Treatment Schedulementioning
confidence: 99%